Fiscal deficits and sustainability of fiscal position in the EU-Countries - Helene Schuberth; Peter Brandner; Leopold Diebalek (European Regional Science Association (ERSA), 1998)
This paper calculates structural balances for EU-countries and relates them to fiscal sustainability. Although the Stability Pact implicitly accepts the need to distinguish between the structural and the cyclical component of net deficits, the issue of long-term sustainability is only covered by the need not to exceed a certain threshold value of the net lending. While the OECD and the European Commission (EU) assume constant elasticities when calculating cyclical budget components to derive structural deficits from the net deficits, the present paper choses time series technique to extract the structural balances directly. = Structural balances are calculated on a disaggregated level considering five different government receipts and expenditure components. With the same method, structural primary balances are estimated to analyse long-term sustainability of fiscal policy in the EU. Therefore, we set the structural primary surpluses against those primary balances, necessary to stabilise the debt to GDP ratio. It is shown that in some of the so-called core-countries like Germany and France, structural surpluses are still below those required to stabilize the debt ratio.
Keywords: 330